Incrassamarin A–D: Four new 4-substituted coumarins from Calophyllum incrassatum and their biological activities. (June 2016) - Aminudin, Nurul Iman; Ahmad, Farediah; Taher, Muhammad; Zulkifli, Razauden Mohamed
Graphical abstract: Highlights: Four new 4-substituted coumarins (1 –4 ) were isolated from Calophyllum incrassatum. . The absolute configurations of (1 ) and (5 ) were determined by X-ray crystallography. The compounds were evaluated for cytotoxic and α-glucosidase inhibitory activities. Compound (1 ) showed the cytotoxic activity against A-549 at IC50 87.71 μg/mL. Compound (1 ) showed inhibitory activity towards α-glucosidase at IC50 93.25 μM. Abstract: Four new 4-substituted coumarins, incrassamarin A (1 ), B (2 ), C (3 ) and D (4 ) with (7 S, 8 S )-7, 8-dihydro-5-hydroxy-7, 8-dimethyl-4-propyl- 2H, 6H -benzo[1, 2- b ;5, 4- b ']dipyran-2, 6-dione (5 ), friedelin, carpachromene, amentoflavone, epiafzelechin and L-quercitrin were isolated from the barks and leaves of Calophyllum incrassatum (Guttiferae). The compounds were isolated and purified by size-exclusion recycling HPLC and column chromatographic techniques. The structures of the compounds were determined by spectroscopic means. The compounds were tested for their cytotoxic activity towards MCF-7 and A-549 cell lines and α-glucosidase enzymatic inhibitory activity. Compound (1 ) displayed cytotoxic activity against A-549 cell lines with IC50 87.71 μg/mL and showed inhibition towards α-glucosidase enzymatic activity with IC50 93.25 μM. This is the first report on the isolation of phytochemicals from the barks and leaves of C. incrassatum and their bioactivities.